Factors related to the active role of the volunteer in the crawl probable case of diphteriae - Alfina, Riza; Isfandiari, Muhammad Atoillah (Faculty of Public Health, 2015)
ABSTRACTDiphtheria is caused by Corynebacterium diphteriae. Children aged 2-10 years are a vulnerable group contracting. Diphteri crawl probable case is difficult, so there are still children who died from diphteri every year. Cadres holds a very important role in the field of public health services so that its presence should be maintained. Level of activity the role of cadres is very dependent on the LKMD role as a manager, and also the public community. This study aims to analyze the factors which associated with a cadres active role in detecting diphteri probable case in Sidoarjo health center. Type of this study is an observational analytic with cross sectional design. Population of this research was all cadres in Sidoarjo health center as much as 516 people. Samples are taken by simple random sampling of 103 respondents. The data was collected using a questionnaire research instruments (questionnaire). The variables of this study is the role of an active cadre to crawl probable case of diphtheria, internal factors (knowledge, attitudes of cadre), external factors (community support, support for community health centers, training of cadres). Techniques of data analysis was done by logistic regression.The results showed 75% of cadres in Sidoarjo health center is active in detecting diphteri probable case. Statistical analysis showed that the internal factors that affect the active role of cadres is the attitude of p = 0.024, external factors are affecting the support of community leaders with p = 0.022, p = 0.042 support community health centers, training of cadres p = 0.041. The advice that can be given is expected that the cooperation between the cadres, community leaders, health center personnel, in support of efforts to increase the capacity and activity of cadres in helping in the field of public health services.Keywords: diphtheria, crawl probable case, cadre, activeness, PHC in Sidoarjo